Ameliorative Effect of Glycyrrhizic Acid on Diosbulbin B-Induced Liver Injury and Its Mechanism - Wang, Xin; Shi, Lei-Lei; Zhang, Yu-Han; Zhu, Hong-Zhe; Cao, Shan-Shan; Shi, Yong; Shangguan, Hui-Zi; Liu, Ji-Ping; Xie, Yun-Dong (The American journal of Chinese medicine (1979), 2025)
This study aimed to clarify the protective effect of Glycyrrhizic acid (GL) against Diosbulbin B (DB) - induced liver injury in mice and investigate its mechanisms of action. A liver injury DB was established in mice through the oral administration of DB for 15 days. At the same time, GL was administered to the mice for treatment. After the experiment, the pharmacodynamics and mechanisms of GL in ameliorating DB-induced liver injury were explored using biochemical indexes, non-targeted metabolomics, targeted metabolomics, Western blotting analysis of protein expression, 16S rDNA sequencing, and Spearman correlation analysis. The results show reduced liver function indices and improved DB-induced hepatic pathological changes. It also attenuated DB-induced hepatic inflammation and oxidative stress. Hepatic metabolomics revealed that GL regulated ABC transporters and bile secretion. Targeted bile acid (BA) metabolomics and Western blotting demonstrated that GL improved DB-induced reduction in BA efflux by regulating FXR-mediated efflux transporters. Furthermore, analysis of 16S rDNA gene sequencing revealed that GL effectively restored the relative abundance of beneficial bacteria, reduced the relative abundance of harmful bacteria, and reinstated the structure of the intestinal flora. Additionally, correlation analyses between BA and intestinal flora indicated that , TDGA, DGA, UDGA, GDGA, THDGA, and HDGA could serve as major markers for DB-induced liver injury. In conclusion, GL significantly improved DB-induced liver injury by increasing the expression of Nrf2/FXR-BSEP/MRP2/P-gp/UGT1A1, promoting BA efflux, regulating intestinal flora, and alleviating inflammation and oxidative stress.